Rare variant analysis in eczema identifies exonic variants in DUSP1, NOTCH4 and SLC9A4 - Sarah Grosche (Nature Portfolio, 2021)
Genetic studies of eczema to date have mostly explored common genetic variation. Here, the authors perform a large meta-analysis for common and rare variants and discover 8 loci associated with eczema. Over 20% of the heritability of the condition is attributable to rare variants.